FDI Impact on Firm Performance in Enlarged Europe: Evidence from a Meta-Regression Analysis - Randolph Luca Bruno; Maria Cipollina (Institute for the Study of Labor (IZA), 2014)
This paper combines, explains and summarizes recent findings from the empirical literature focusing on the FDI's effect on firms' performances by collecting all the relevant firm level quantitative studies to run a regression of regressions focused on Enlarged Europe. The results show that there exists a positive indirect impact of FDI on productivity and ultimately on economic growth in EU, but it is limited in magnitude. Moreover, the effect of FDI on growth is stronger for New EU Members after 2001.
Keywords: C81; F23; O52; 330; firm performance; Enlarged Europe; meta-regression analysis